On The WH Question Particle [Wo] In Yorùbá̀ - Timothy Adeyemi Akanbi (European Scientific Journal, ESJ, 2016)
Every language has markers which are used in order to turn a positive sentence to an interrogative one; and native speakers of such language know the appropriate marker to use in any particular structure in order to ask questions or elicit information. Many of the WH question markers in Yorùbá are composed of one word. However, the question particle …wo ‘when/which36’ which is the focus of this paper, appears to be different in that it is composed of more than one word in its occurrence before it can function as a WH question marker. The focus of this paper is on this particular WH question particle (…wo) in Yorùbá. I argue that this particle is composed of more than one word before it can function as a question marker and turn a positive sentence to an interrogative one. In other words it must combine with either a prepositional phrase (PP) or a noun phrase (NP) and thereafter move to Spec-CP through movement rule of internal merge to check its WH interrogative feature for proper convergence at Spell-Out.